Low aerobic capacity in middle-aged men associated with increased mortality rates during 45 years of follow-up. (September 2016) - Ladenvall, Per; Persson, Carina U; Mandalenakis, Zacharias; Wilhelmsen, Lars; Grimby, Gunnar; Svärdsudd, Kurt; Hansson, Per-Olof
Background: Low aerobic capacity has been associated with increased mortality in short-term studies. The aim of this study was to evaluate the predictive power of aerobic capacity for mortality in middle-aged men during 45-years of follow-up. Design: The study design was a population-based prospective cohort study. Methods: A representative sample from Gothenburg of men born in 1913 was followed from 50–99 years of age, with periodic medical examinations and data from the National Hospital Discharge and Cause of Death registers. At 54 years of age, 792 men performed an ergometer exercise test, with 656 (83%) performing the maximum exercise test. Results: In Cox regression analysis, low predicted peak oxygen uptake (VO 2 max ), smoking, high serum cholesterol and high mean arterial blood pressure at rest were significantly associated with mortality. In multivariable analysis, an association was found between predictedVO 2 max tertiles and mortality, independent of established risk factors. Hazard ratios were 0.79 (95% confidence interval (CI) 0.71–0.89; p < 0.0001) for predictedVO 2 max, 1.01 (1.002–1.02; p < 0.01) for mean arterial blood pressure, 1.13 (1.04–1.22; p < 0.005) for cholesterol, and 1.58 (1.34–1.85; p < 0.0001) for smoking. The variable impact (Wald's χ 2 ) of predictedVO 2 max tertiles (15.3) on mortality was secondary only to smoking (31.4). The risk associated with low predictedVO 2 max was evident throughout four decades of follow-up. Conclusion: In this representative population sample of middle-aged men, low aerobic capacity was associated with increased mortality rates, independent of traditional risk factors, including smoking, blood pressure and serum cholesterol, during more than 40 years of follow-up.